2004
DOI: 10.1063/1.1778164
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fluid deuterium under double-shock compression to several Mbar

Abstract: The compressibility of fluid deuterium up to several Mbar has been probed using laser-driven shock waves reflected from a quartz anvil. Combining high-precision (∼1%) shock velocity measurements with the double-shock technique, where differences in equation of state (EOS) models are magnified, has allowed better discrimination between theoretical predictions in the second-shock regime. Double-shock results are in agreement with the stiffer EOS models—which exhibit roughly fourfold single-shock compression—for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 37 publications
5
42
0
1
Order By: Relevance
“…In those experiments, temperature was not measured but later experiments using reflectivity and emissivity, to infer the temperature (Bailey et al, 2008) are shown in figure 13, and found to be in good agreement with previous data. Also, second-shock data up to 900 GPa has been measured with laser-driven shocks at OMEGA laser in Rochester (Boehly et al, 2004). These data are consistent with a stiff EOS with 4.3 to 4.4-fold maximum compression along the principal Hugoniot.…”
Section: Fig 11 (Color Online)supporting
confidence: 63%
“…In those experiments, temperature was not measured but later experiments using reflectivity and emissivity, to infer the temperature (Bailey et al, 2008) are shown in figure 13, and found to be in good agreement with previous data. Also, second-shock data up to 900 GPa has been measured with laser-driven shocks at OMEGA laser in Rochester (Boehly et al, 2004). These data are consistent with a stiff EOS with 4.3 to 4.4-fold maximum compression along the principal Hugoniot.…”
Section: Fig 11 (Color Online)supporting
confidence: 63%
“…For this reason, most of the recent experimental measurements by shock compression have focused on the heavier isotope [11][12][13][14][15][16] . However, it should be noted that the Hugoniots for the two isotopes do not scale in density.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, The EOS of hydrogen and helium in the fluid regime have been studied through gas gun [38], chemical explosive [39], magnetic driven plate flyer [40], and high power laser [41][42][43]. Since these experiments were limited by the conservation of mass, momentum, and energy, the explored density of warm dense matter were limited within 5 ∼ 6 times of the initial density.…”
Section: A the Equation Of Statementioning
confidence: 99%